Perlindungan Hukum Bagi Pembeli Akibat Penolakan Ahli Waris Penjual yang Menimbulkan Wanprestasi Akta Pengikatan Jual Beli (Studi Putusan No.648/Pdt.G/2020/PN.Jkt.Utr) - Indri Romauli Marbun, Luya; Ikhsan, Edy; Kaban, Maria (UNES Law Review, 2024)
Sale and purchase agreements are one form of agreement that often occurs in society. An agreement will be valid if it has fulfilled the conditions stipulated in Article 1320 of the Civil Code. The sale and purchase binding deed is a preliminary agreement that binds the parties to the sale and purchase and has the right and obligation to fulfill the performance as agreed upon in the sale and purchase agreement. The research method used is normative juridical research. The nature of this research is descriptive analytical. The source of legal material used is secondary data with primary legal materials, secondary legal materials and tertiary legal materials. The research technique used is library research with a case approach to this research. The results of this study indicate that defaults caused by heirs who are reluctant to pay land and building tax and seller's tax from the late seller / heir in the deed of binding of sale and purchase even though the buyer has carried out his performance so as to obtain legal protection, he filed a lawsuit with the court in accordance with preventive legal protection.